Returns to Skills and Personnel Management: U.S. DoD Scientists and Engineers - Michael Gibbs (Institute for the Study of Labor (IZA), 2005)
Personnel records are used to examine compensation, recruitment, and retention of a group of very highly skilled workers: civilian scientists and engineers in U.S. Department of Defense laboratories. In contrast to the private sector, returns to skills were largely flat for this group from 1982-1996. Despite this, quality and performance of recruits relative to earlier cohorts, and of those retained relative to those who left, remained stable. One explanation is the importance of defense-industry-specific human capital. These results hold for three different pay plans, including the federal government?s primary plan and two intended to introduce greater flexibility in personnel management.
Keywords: J44; J31; J24; J45; 330; returns to skills; personnel; workforce quality; Bildungsertrag; Personalwirtschaft; Militär; Wissenschaftler; Ingenieure; USA